Evolution of Gender Gaps in Latin America at the Turn of the Twentieth Century: An Addendum to New Century, Old Disparities - Alejandro Hoyos; Hugo Nopo (Inter-American Development Bank (IDB), 2010)
This paper complements the findings of Atal, \~Nopo and Winder (2009) on gender and ethnic wage gaps for 18 Latin American countries circa 2005 by analyzing gender wage gaps for the same countries between circa 1992 and circa 2007. During this span the overall gender earnings gaps dropped about 7 percentage points, while the unexplained component dropped between 3 and 4 percentage points, depending on the control variables used. The gap declined most notably among workers at the bottom of the earnings distribution, with children at home, the self-employed, part-time workers and those in rural areasthe segments of the labor market that were previously reported as having the highest unexplained gender disparities. Most of the reduction in unexplained gaps occurred within segments rather than due to the composition of labor markets. The paper additionally finds a limited role for job tenure in explaining gender wage gaps.
Keywords: C14; D31; J16; O54; 330; Gender; Wage gaps; Latin America; Matching